TRANSFORMATIONAL PARTNERSHIPS: DEVELOPING EFFECTIVE UNIVERSITY-ENTERPRISE COOPERATION - Krouglov, Alex (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This paper deals with the engagement of Higher Educational Institutions (HEIs) with the outside world, and how academic institutions build their relations with public, private and professional organisations. The research explores university-enterprise relations and the issues of employability of students in the 21st century, how universities respond to new demands and requirements in this field. The current research is based on the analysis of strategic planning in UK universities and considers several case studies as examples of developing mutually beneficial ‘transformational’ university-enterprise partnerships. The research analysis of the collected data aims to explore the importance of university-enterprise partnerships for students, academics, universities, and employers and how universities ensure effective developments in the field. The results of the research show that strategic planning is key in developing effective university-enterprise relations, and the strategic targets can only be achieved when there is evidence of active engagement of university staff and students in the process cooperation with enterprises.